Aspectos relevantes das astreintes no cumprimento das decisões judiciais - Kabbach, Matheus Garrido de Oliveira (2012)
The monograph herein deals with significant matters relating to the astreintes, both from the doctrine and from the Brazilian jurisprudence standpoints. The development of the essay begins with the presentation of a brief clarification of the matter at hand, in which the importance of coercive fines in the current Brazilian procedural system is approached, mainly with regard to the effectiveness of court decisions. Subsequently, the legislative evolution of the matter in Brazil, as well as the concept itself, its purposes within the procedural system and the legal nature of the astreintes are further discussed. In relation with the practical use of the astreintes, this paper approaches the moment of the establishment of the fine by the judge, the criteria adopted in connection therewith, the limits between the quantum of the fine and the value of the breached obligation, the existence or the absence of a maximum value in the context of Law n. 9.099/95, as well as the eventual possibility of accumulation of amounts arising from the application of said fine. Furthermore, the moment in which the credit that arises in connection with the astreintes is due is also analysed, as well as the means and the possibility of execution of the amounts accrued by virtue of the application of the fine. Finally, in conclusion, certain personal notes taken from the interpretation of each of the topics dealt herewith are also made